Preschoolers' self-regulation, skill differentials, and early educational outcomes - Johanna Sophie Quis; Anika Bela; Guido Heineck (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Are there differentials in children's competence levels by their self-regulation and do they imply differences in competence development? We investigate the relationship between preschoolers' self-regulation and their mathematical competence and its development using data from the German National Educational Panel Study (NEPS). Our results imply a positive association between self-regulation and mathematical competence levels, even when holding general cognitive ability constant. Self-regulation is generally not related to competence development over the first two years of primary school. Children with low initial mathematical competence, however, benefit at the transition to primary school, but no between grades 1 and 2.
Keywords: J24; 330; Self-regulation; Skill formation; Competence development